Del « mono del desencanto » al nuevo malestar temporal: herencias y bloqueos históricos en la crisis de la modernidad democrática española - Germán Cano (Cahiers de Civilisation Espagnole Contemporaine)
If we understand the problem of memory in the so-called « Spanish democratic modernity » also as a problem of relationship with its present, of what kind of present we want, what we are currently witnessing in certain conservative sectors in Spain is not so much a return to the past as a certain usurious return to the past of presentist positions that try to legitimise themselves by preventing any fruitful and more metabolic relationship with our history. In this sense, we could speak of a specific return under conditions of an authoritarian present that is, above all, short-termist and extractivist in accordance with its own quest for profit exploitation (hence its closeness to the postmodern pastiche). Moreover, is this not a past that is invoked in the present all the more violently to protect itself from the future, indeed, that does not want a future, that is even afraid of it? In this intervention I would like to dwell on these questions in the comparative light of two historical scenarios: the problematic of the so-called Spanish disenchantment and the question of the « indignados » in the 2011-2015 political cycle.